Análisis de coherencia de los proyectos de grado del programa de Licenciatura en Educación Básica con Énfasis en Educación Física, Recreación y Deporte de la UCEVA, con las áreas fundamentales de la educación básica (2014)
The objective of this project was to demonstrate the coherency of essays presented for the students in basic education with an emphasis in physical education, recreation and sports, of the UCEVA between 2008 and 2012, and relate their affinity with the fundamental areas of basic education, according to the law 115 of 1994, or general education law, and identify thematic trends and their correspondence with the research program. The development the project allowed an exploration for academic purposes in the context of currently changes in the curriculum, being an important input for analysis and auto-evaluation looks regarding the training of future graduates; also provides the approach by the developers, with the ratification of the hypothesis that states the majority of degree work in the program, are inclined towards research emphasis, taken as a competitive advantage that would project changes gradually, not looking as weakness despite the need to strengthen some aspects of other fundamental areas. The project by his characteristics of interaction with information, professors, students and graduates, allowed a strengthening in the comprehensive conception of the institution contribution to the educational areas to form these graduates and also graduates with society to contribute with their efforts in educational institutions. All this is captured in the reading of the final report from the opening chapter to the recommendations.